Differences Between the Psychiatric Symptoms of Healthcare Workers Quarantined at Home and in the Hospital After Contact With a Patient With Middle East Respiratory Syndrome - Seong, Su Jeong; Kim, Hyung Joon; Yim, Kyung Mi; Park, Ji Won; Son, Kyung Hoon; Jeon, Yeong Ju; Hwang, Jae Yeon (Frontiers in Psychiatry, 2021)
Objective: Although quarantine is an effective measure for the prevention of the spread of infectious diseases, it may have negative effects on the mental health of the isolated individual. During the 2015 outbreak of the Middle East Respiratory Syndrome (MERS) in Korea, healthcare workers came in contact with patients with MERS were quarantined either at home or in a hospital ward. In this study, we aimed to compare the psychiatric symptoms of these employees according to the method of quarantine. Methods: All 146 quarantined staff completed self-report questionnaires. Depressive symptoms were measured using the Patient Health Questionnaire-9, anxiety symptoms were assessed using Spielberger's State-Trait Anxiety Inventory, and acute stress disorder (ASD) symptoms were evaluated using the Stanford Acute Stress Reaction Questionnaire. Results: The in-hospital quarantine group had a higher rate of symptoms of depression (p < 0.001) and ASD (p = 0.014) than the group quarantined at home. Logistic regression analysis showed that respondents quarantined in the hospital (OR = 6.342; 95% CI 1.853–21.708) and those quarantined for longer periods (OR = 1.153, 95% CI = 1.036–1.285) had a higher risk of depressive symptoms. Conclusions: In-hospital quarantine and quarantine for longer periods increase the risk of depressive symptoms. When quarantine measures are taken, certain measures are needed to minimize the risk of psychiatric problems. Appropriate interventions should be implemented if psychiatric problems occur.